Peran Institusi Pengajian di Kalangan Perempuan Banjar (Studi atas Pengajian Ar-Rahmah Sekumpul Martapura) - Alfisyah, Alfisyah (Muadalah, 2015)
Moslem recitals (pengajian) as an Islamic educational institution has a very long presence which until now are still survive despite the emerging modern educational institution. Its existance is inseparable from its significant role to modify itself, keep developing and to maintain its principle values. To uncover the survival of the institution, the writer has conducted a study that aims at describing the roles that have been done by Ar-Rahmah Sekumpul Martapura Recitals. Through a qualitative study method conducted in Ar-Rahmah Sekumpul, Martapura-South Kalimantan, it is identified that Ar-Rahmah has not only played the educative role for the women of Banjar, but also maintained the Islamic tradition as well as the role of the economy through cooperation and capital accumulation